A Pushing Approach for Data Synchronization in Cloud to Reduce Energy Consumption in Mobile Devices - Carvalho, S. A. L.; Lima, Rafael Nunes de; Silva-Filho, Abel Guilhermino da (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2014: Anais do IV Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2014)
With the increase in smartphone sales and the use of clouds, data synchronization is an essential activity in the mobile applications that aim to keep data up-to-date with information from the application server. This paper proposes an analysis of the main approaches for data synchronization concerning energy, which are the polling and pushing techniques. The results show a substantial gain in terms of energy consumption for the pushing technique when compared to the polling technique in mobile applications. An experimental environment based on Arduino and INA219 that allows current and voltage acquisition of 138 samples per second was used. Results showed a significant increase of 187% in terms of energy consumption when the polling technique was applied, which was more advisable than the use of the polling technique when one or more requests in a forty minute range are not necessary to be made.